Cancer predisposition syndromes as a risk factor for early second primary neoplasms after childhood cancer – A national cohort study. (March 2021) - Waespe, Nicolas; Belle, Fabiën N.; Redmond, Shelagh; Schindera, Christina; Spycher, Ben D.; Rössler, Jochen; Ansari, Marc; Kuehni, Claudia E.; Ansari, Marc; Beck-Popovic, Maja; Bourquin, Jean-Pierre; et al.
Abstract: Background: Childhood cancer patients are at increased risk of second primary neoplasms (SPNs). We assessed incidence and risk factors for early SPNs with a focus on cancer predisposition syndromes (CPSs). Patients and methods: This cohort study used data from the Swiss Childhood Cancer Registry. We included patients with first primary neoplasms (FPNs) diagnosed before age 21 years from 1986 to 2015 and identified SPNs occurring before age 21. We calculated standardised incidence ratios (SIRs) and absolute excess risks (AERs) using Swiss population cancer incidence data, and cumulative incidence of SPNs. We calculated hazard ratios (HRs) of risk factors for SPNs using Fine and Gray competing risk regression. Results: Among 8074 childhood cancer patients, 304 (4%) were diagnosed with a CPS and 94 (1%) developed early SPNs. The incidence of SPNs was more than 10-fold higher in childhood cancer patients than the incidence of neoplasms in the general population (SIR = 10.6, 95% confidence interval [CI]: 8.7–13.1) and the AER was 179/100, 000 person-years (CI: 139–219). Cumulative incidence of SPNs 20 years after FPN diagnosis was 23% in patients with CPSs (CI: 12–41%) and 2.7% in those without (CI: 2.0–3.6%). Risk factors for SPNs were CPSs (HR = 7.8, CI: 4.8–12.7), chemotherapy (HR = 2.2, CI: 1.1–4.6), radiotherapy (HR = 1.9, CI = 1.2–2.9), haematopoietic stem cell transplantation (HR = 1.8, CI: 1–3.3), and older age (15–20 years) at FPN diagnosis (HR = 1.9, CI: 1.1–3.2). Conclusion: CPSs are associated with a high risk of SPNs before age 21 years. Identification of CPSs is important for appropriate cancer surveillance and targeted screening. Graphical abstract: Image 1 Highlights: The incidence of second primary neoplasms (SPNs) before age 21 years was 10-fold higher after childhood cancer compared to the general population. Cancer predisposition syndromes (CPSs) were the strongest predictor of SPNs. The cumulative incidence of SPNs was 23% (95%CI 12–41%) in CPSs after 20 years of follow-up.